2023
DOI: 10.48550/arxiv.2301.12697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Likely detection of gamma-ray pulsations of PSR~J1717+4308A in NGC~6341 and implication of the gamma-ray millisecond pulsars in globular clusters

Abstract: We report our analysis results for the globular cluster (GC) NGC 6341 (M92), as a millisecond pulsar (MSP) J1717+4308A has recently been reported found in this GC. The data used are from the Large Area Telescope onboard the Fermi Gamma-ray Space Telescope (Fermi). We detect γ-ray pulsations of the MSP at a 4.4σ confidence level (the corresponding weighted H-test value is ∼28.4). This MSP, the fourth γ-ray pulsar found in a GC, does not have significant off-pulse emission and has γ-ray luminosity and efficiency… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…109 The fastest known field MSP, PSR J0952−0607, was found at the location of a gamma-ray source and subsequently timed with LAT data (Bassa et al 2017b;Nieder et al 2019). A third globular cluster, NGC 6652, was found to have gamma-ray emission dominated by a single MSP, PSR J1835−3259B (Gautam et al 2022b;Zhang et al 2022), with a fourth recently reported, PSR J1717+4308A in M92 (Zhang et al 2023). The gamma-ray flux and pulse profile of PSR J2021+4026 in the γ Cygni supernova remnant (SNR) changed during mode transitions in 2011 and 2018 (Allafort et al 2013;Razzano et al 2023).…”
Section: Introductionmentioning
confidence: 93%
“…109 The fastest known field MSP, PSR J0952−0607, was found at the location of a gamma-ray source and subsequently timed with LAT data (Bassa et al 2017b;Nieder et al 2019). A third globular cluster, NGC 6652, was found to have gamma-ray emission dominated by a single MSP, PSR J1835−3259B (Gautam et al 2022b;Zhang et al 2022), with a fourth recently reported, PSR J1717+4308A in M92 (Zhang et al 2023). The gamma-ray flux and pulse profile of PSR J2021+4026 in the γ Cygni supernova remnant (SNR) changed during mode transitions in 2011 and 2018 (Allafort et al 2013;Razzano et al 2023).…”
Section: Introductionmentioning
confidence: 93%